Christ and the Old Covenant: Francis Turretin (1623-1687) on Christ's suretyship under the Old Testament - Gwon, Gyeongcheol (Reformed Historical Theology, 2018)
Angaben zur beteiligten Person Gwon: Gyeongcheol Gwon, Ph.D., is Lecturer in Church History at Kukje Theological University and Seminary in Seoul, Korea.